Bibliometric Analysis of Digital Da'wah - Loso Judijanto (West Science Islamic Studies, 2026)
The rapid development of digital technology has transformed the practice of Islamic preaching (da'wah), shifting from conventional communication methods toward digital platforms that enable broader and more interactive religious engagement. This study aims to explore the intellectual structure, publication trends, influential contributions, collaboration patterns, and emerging research themes in the field of Digital Da'wah using a bibliometric analysis approach. Data were retrieved from the Scopus database using relevant keywords related to digital da'wah, online preaching, Islamic communication, and digital religion. The collected publications were analyzed using VOSviewer to visualize co-authorship networks, country collaborations, citation patterns, keyword co-occurrence, thematic evolution, and research density. The findings indicate that Digital Da'wah research has grown significantly, with Indonesia emerging as the most prominent contributor and the primary collaboration center. The literature analysis shows that early research focused mainly on social media utilization, Islamic communication, and online religious dissemination. However, recent studies have expanded toward broader issues, including digital religious authority, mediatization, digital platforms, artificial intelligence ethics, content automation, and ethical technology. The keyword analysis reveals a transition from platform-oriented studies toward interdisciplinary discussions involving communication studies, Islamic studies, and technological innovation. This study concludes that Digital Da'wah has developed into a multidimensional research field reflecting the transformation of religious practices in the digital era. Future research should further investigate ethical frameworks for AI-assisted da'wah, digital religious literacy, algorithmic influence on Islamic content distribution, and sustainable digital religious communities.